1990
DOI: 10.1038/345224a0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor that identifies a novel retinoic acid response pathway

Abstract: Molecular cloning and transcriptional activation studies have revealed a new protein similar to the steroid hormone receptors and which responds specifically to vitamin A metabolites. This protein is substantially different in primary structure and ligand specificity from the products of the previously described retinoic acid receptor gene family. By indicating the existence of an additional pathway through which retinoic acid may exert its effects, these data lead to a re-evaluation of retinoid physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
686
0
15

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,430 publications
(712 citation statements)
references
References 46 publications
11
686
0
15
Order By: Relevance
“…A CAT reporter gene containing the palindromic (inverted repeat) element TREp, which can be activated by both RARs and RXRs (47,66), was used. Figure 2A shows that as expected, RA and 9-cis RA activated transcription by both RARs and RXRs (38,44,47,66). However, SR11237 selectively activated RXRot-dependent transcription -22-fold over the control (vehicle alone) level, and RXR-y mRNAs were barely detectable in JEG-3 cells by Northern analysis (data not shown).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A CAT reporter gene containing the palindromic (inverted repeat) element TREp, which can be activated by both RARs and RXRs (47,66), was used. Figure 2A shows that as expected, RA and 9-cis RA activated transcription by both RARs and RXRs (38,44,47,66). However, SR11237 selectively activated RXRot-dependent transcription -22-fold over the control (vehicle alone) level, and RXR-y mRNAs were barely detectable in JEG-3 cells by Northern analysis (data not shown).…”
mentioning
confidence: 99%
“…Retinoid binding by RXR may further modulate the transcriptional response to T3 and vitamin D in some cases (13,39,51,65). However, regulation of gene expression by RA is more complicated because of the coexistence of two families of retinoid receptors, RA receptors (RARs) and RXRs (15,40,43,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional effects of retinoids are mediated by their interactions with RARs (Giguere et al, 1987;Petkovich et al, 1987;Brand et al, 1988;Krust et al, 1989) and RXRs (retinoid receptors) (Mangelsdorf et al, 1990;Mangelsdorf et al, 1992) which are members of the steroid-thyroid hormone superfamily of nuclear receptors. The RARs bind all-trans-RA and its stereoisomers 9-cis-RA and 13-cis-RA (Allenby et al, 1993).…”
mentioning
confidence: 99%
“…[10][11][12][13] In 1990, the family of retinoid 'X' receptors (RXRs) was described, which were shown to act as cofactors for RARs as well as receptors for vitamin D, thyroid hormone and peroxi-some proliferation-associated proteins. [14][15][16][17] Whereas all-trans RA binds only RARs, 9-cis RA binds and activates both RARs and RXRs. [18][19][20] Preclinical studies also showed that 9-cis RA was more potent than all-trans RA in inducing myeloid differentiation in HL60 cells.…”
Section: Introductionmentioning
confidence: 99%